Influence of infected root dentin on the bond strength of a self-adhesive resin cement - Débora Delai; Maybell Tedesco; Josiane de Almeida; Marcelo Carvalho Chain; Cleonice da Silveira Teixeira; Mara Cristina Santos Felippe; Wilson Tadeu Felippe (Wolters Kluwer Medknow Publications, 2018)
Aim: The aim of this study was to determine the bond strength (BS) of a self-adhesive resin cement to the contaminated root dentin. Materials and Methods: The crown and apical third of twenty single-rooted teeth were removed. The root canals were flared and 1-mm-thick root sections were obtained. The sections were rinsed, dried, and sterilized. The control group (n=20) was composed of one section of each third, which remained immersed in sterile trypticase soy broth (TSB) for 2 months. The other sections comprised the experimental group (n = 40) and were immersed in a suspension of Enterococcus faecalis. The culture medium was changed at every 4 days for 2 months. The sections were rinsed with distilled water, dried, and the root canal space was fi lled with the self-adhesive resin cement RelyX™ U200. After 24 h, the push-out test was performed and the types of interface failure were observed on a stereo microscope. Statistical Analysis: Data were statistically analyzed by the nonparametric Mann-Whitney test (α=5%). Results: A significant reduction was observed in the BS of resin cement to the contaminated dentin compared to the healthy dentin, for both thirds analyzed (P < 0.05). The BS was signifi cantly greater at the cervical third compared to the middle third for specimens in the experimental group (P < 0.05). Adhesive and mixed failures were observed more frequently in specimens contaminated with E. faecalis. Conclusion: Bacterial contamination negatively infl uenced the BS of the self-adhesive resin cement to the root dentin, and there was a predominance of adhesive and mixed failures.